Решите уравнение методом замены переменной. Впишите ответ. (x + 1)^4 + x^2 = –1 – 2xЕсли x ≠ 0.Ответ: x =
(x + 1)⁴ +x² = - 1 - 2x
(x + 1)⁴ + (x² + 2x + 1) = 0
(x + 1)⁴ + (x + 1)² = 0
(x + 1)² = m , m ≥ 0 ⇒ (x + 1)⁴ = m²
m² + m = 0
m(m + 1) = 0
или m₁ = 0
или m + 1 = 0 и тогда m₂ = - 1 < 0 - неуд
(x + 1)² = 0
x + 1 = 0
x = - 1
Ответ : - 1
(x + 1)* +x2 = - 1 - 2x (x + 1)* + (x2 + 2x + 1) = 0 (x + 1)* + (x + 1)2 = 0 (x + 1)2 = m m 0 (x + 1)* = m2 m? + m = 0 m(m + 1) = 0 или = 0 или m+1 = 0 и тогда = - 1 < 0 - неуд (x + 1)2 = 0 x + 1 = 0 x = - 1 Ответ : - 1